Development and evaluation of an oral presentation module using interactive white board for foundation students / P.Thivilojana S.Perinpasingam - P.Thivilojana , S.Perinpasingam (2018)
The purpose of this study was to develop and evaluate an oral presentation module in a foundation classroom. This module was implemented for students from a foundation programme in a selected private higher education in the Klang Valley. A development research method based on ADDIE’s model was selected. This technique was divided into with three phase’s needs analysis, design and development and implementation and evaluation. Data from the needs analysis phase was mainly from a survey done by students and a semi-structured interview involving the Programme Director and a lecturer, while the second and the third phase was done concurrently. In the second phase, interviews were carried out with experts and for the third phase, the implementation and evaluation phase, data was gathered from surveys and interviews involving students who have used the Interactive White Board as a presentation tool.In the first phase, the needs analysis included a survey of technology usage of 145 students from a foundation programme in a selected private higher learning institution in the Klang Valley. The findings indicated the respondents perceived themselves to be skilled in the usage of computers. A large number of students were familiar with the usage of power point slides as a presentation tool and some were already familiar with the usage of Interactive White Board. The participants believed that Interactive White Board was important for the teaching and learning process in the English classroom in particular to be used an interactive presentation tool. In addition to that, the interview findings have revealed that these students will be able to produce an engaging presentation using the Interactive White Board if proper guidance and training were given to these students. From the findings of the first phase, an interactive presentation module was developed. In the second phase of design and development, the interactive presentation module was designed based on Kristaf and Saftan’s (1995) interactive learning system which can be divided into three areas namely information design, interaction design and presentation design. A constructivist method was used with the interactive presentation module for the delivery of the classroom resources in the design process. A group of five experts were selected for this phase. Two of them were experts in instructional technology and the other three were English language lecturers who were the subject matter experts. These experts highlighted issues based on information design, presentation design and interactive design. Findings obtained from the experts reveal that module was interesting, appealing and supports interactive presentation. In the third phase, which is implementation and evaluation phase were carried out. During the implementation stage, the researcher was the coordinator of the module. Data was collected from surveys done by the students from both groups namely the dependent (presentation with Powerpoint) and the independent group (presentation with Interactive White Board) and an interview with a group of 10 foundation students who had used the Interactive White Board to conduct an interactive presentation. The data was gathered to analyse the student’s perception on using the Interactive White Board as a presentation tool and the compare students ’achievements. Based on the findings, it is suggested that an oral presentation module using Interactive White Board could be used for learning of English, as well as other subjects.